Sistema de monitoreo y recopilación de datos para evaluar la calidad de energía y consumos en la cámara de transformación N°2 en la Universidad Técnica de Cotopaxi, Campuz la Matriz, periodo 2020. - Moreta Corella, Daniela Elizabeth (2020)
This technological proposal is focused on the study of energy quality in the Transformation Chamber (CT) No. 2 of the Technical University of Cotopaxi, due to intrinsic factors that have occurred in the computer equipment and personal equipment used in The network that supplies the circuit, when the computer center is operating, it is appreciated that there is a prominent variation in voltage in the equipment, this has caused many to be damaged in the power source, especially the laptops, in addition to the consumption energy has never been valued in this energy center, much less its behavior with respect to its charges and disturbances is known. The main objective is to implement an electrical monitoring system for the evaluation of the power quality in the CT, for this the methodology used had a quantitative approach because it works with metrics of power, voltage, frequency, current, power factor, THD to estimate and interpret whether the energy meets national or international standards and parameters. Among the results revealed, it is obtained that the THD is excessive and does not meet a nominal value because the power factor in the measurements does not comply whith 0.92 established by the standard, in addition there are oscillating overvoltage events and disturbance problems caused by electromechanical noise derived from nearby facilities; Regarding quality, it can be estimated that the network requires maintenance and decision-making.